(untitled) (Revista de Investigaciones Universidad del Quindío, 2017)
Several authors have reported the role of DNA methylation on IDS gene as a possible explanation of X chromosome inactivation. Besides, patients who suffer from mucopolysaccharidosis show a skewed X chromosome inactivation pattern related to a low or none iduronate-2-sulfatase activity. We reported a consisted pattern of transitional mutation c.438C>T on relative females of MPS II patients due to point mutations c.641C>T, and c.1122C>T. From several bioinformatics analysis we found an association between the inherited deamination mechanisms, responsible to avoid skewed X inactivation, and transitional mutations on pathogenic spots along IDS gene. Besides, data analysis predicted a possible increasing on pathogenic mutations on IDS gene. We consider this finding very valuable to propose a broad screening on fertile females of methylation target spots in X chromosome. Results from these screening test would help to prevent allele frequency increasing on X linked diseases as MPS, Lesch-Nyhan syndrome, and Duchenne muscular dystrophy.